Knowledge and Awareness of Cervical Cancer among HIV-Infected Women in Ethiopia - Netsanet Shiferaw; Mohamad I. Brooks; Graciela Salvador-Davila; Shumet Lonsako; Konjit Kassahun; Jodi Ansel; Chidude Osakwe; Teklu Weldegebreal; Ismael Ahmed; Mengistu Asnake; Paul D. Blumenthal (Hindawi Limited, 2016)
Introduction. Cervical cancer is one of the leading causes of cancer death among Ethiopian women. Low awareness of cervical cancer, in combination with low health care seeking behavior, is a key challenge for cervical cancer prevention. This study assessed the knowledge of cervical cancer among HIV-infected women in Ethiopia. Methods. A facility-based cross-sectional survey was conducted from August to September 2012 among HIV-infected women between 21 and 49 years of age. Basic descriptive statistics were performed using SPSS. Results. A total of 432 HIV-infected women participated in this study. About 71% of participants had ever heard of cervical cancer. Among women who had ever heard of cervical cancer, 49% did not know the cause while 74% were able to identify at least one risk factor for cervical cancer. Only 33% of women were able to correctly address when women should seek care and 33% identified at least one treatment option for cervical cancer. Conclusion. This study revealed that knowledge about cervical cancer was generally low, in particular for health care seeking behavior and treatment of cervical cancer. Health awareness programs should be strengthened at both community and health facility levels with emphasis highlighting the causes, risk factors, care seeking behaviors, and treatment options for cervical cancer.